Articulating lifelong learning in tourism : dialogue between humanities scholars and travel providers : final report. - Broomhall, Susan; Pitman, Tim; Majocha, Elzbieta; McEwan, Joanne (Australian learning and teaching council, 2010)
The project team investigated the points of view of academic staff involved in educational tourism, the educational tourism sector and clients' expectation of their tourism experience. Reasons for increased involvement of universities in educational tourism are presented.